2021
DOI: 10.2147/prbm.s322348
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioural Consistency Value Seeking of Tourists in Niche Tourism: Nostalgia, Authenticity Perception, and Satisfaction

Abstract: Introduction:This study proposed a model based on Izard's theory of differential emotions to examine the effects of heritage nostalgia on perceived authenticity towards tourist satisfaction and the moderation of self-congruity in Chinese niche tourism. Methods: We examined descriptive statistics to obtain an overview of the sample by using computer program SPSS 22. Then, for evaluation, partial least squares structural equation modelling (PLS-SEM) was employed as the appropriate statistical tool, and the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…This study found that most of the respondents would evaluate the past tourism experiences before they decided to visit a tourism destination. This finding was supported by a previous study which concluded that the positive experience at the previously visited tourism destination would increase the level of satisfaction (Zhou et al, 2021). Further, Gao et al (2020) confirmed that there was an impact of nostalgia on the tourist satisfaction in heritage tourism destinations.…”
Section: Figure 2 Results Of Structural Model Testingsupporting
confidence: 77%
See 2 more Smart Citations
“…This study found that most of the respondents would evaluate the past tourism experiences before they decided to visit a tourism destination. This finding was supported by a previous study which concluded that the positive experience at the previously visited tourism destination would increase the level of satisfaction (Zhou et al, 2021). Further, Gao et al (2020) confirmed that there was an impact of nostalgia on the tourist satisfaction in heritage tourism destinations.…”
Section: Figure 2 Results Of Structural Model Testingsupporting
confidence: 77%
“…The tourist satisfaction referred to the results of the tourists' emotional experience based on the contradiction of expectations generated from comparisons between the expectations before and after the experience. In other words, the satisfaction was the end result of the emotional or affective response (Gao et al, 2020;Leong, Yeh, Hsiao, & Huan, 2015;Renko & Bucar, 2014;Zhou et al, 2021). The tourist satisfaction was influenced by the happiness in the past experiences.…”
Section: Figure 2 Results Of Structural Model Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 270 valid questionnaires were finally obtained. The sample size is 10.8 times the number of model parameters, in addition to the above mentioned criteria, combined with some studies in the field of tourism, such as Xiang et al 57 and Zhou et al, 135 which show the sample size meets the requirements.…”
Section: Methodsmentioning
confidence: 99%
“…The local community can also be able to create something according to their respective fields so that later it can be sell to tourists that visiting the tourism village (Perles-Ribes et al, 2021;Kattiyapornpong, Ditta-Apichai, & Chuntamara, 2022;Boto-García, 2022;Moral-Cuadra et al, 2022). Through the development of tourism villages, it is hoped that local communities can improve their welfare through sustainable tourism development (Piramanayagam, Sud, & Seal, 2021;Yasami, Promsivapallop, & Kannaovakun, 2021;Zhou et al, 2021;Sangkaew, Nanthaamornphong, & Phucharoen, 2023). In addition, the development of tourist villages can also help promote the cultural and environmental wealth of the area.…”
Section: Introductionmentioning
confidence: 99%